(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
EFL (English as a Foreign Language) courses sometimes struggle to bring the authenticity of language to their students. Similar circumstances can occur in situations with ESL (English as a Second Language) students that return to a home that does not speak English. Some countries attempt to remedy this by bringing in native English speakers to co-teach EFL classes. Immersive education functions at its best when students are able to interact with their peers in a low-stakes environment. At the University of Toledo, there is a program in place where Japanese exchange students can interact with native English speaking students during a lunch period. Virtual reality headsets could be used to recreate this program without having to travel overseas.